PERANAN ADVOKAT DALAM UPAYA PENYELESAIAN PERBUATAN MELANGGAR HUKUM MELALUI MEDIASI - Rifka Youlanda Margareth Hutagalung; Lesson Sihotang (JOURNAL OF LAW AND NATION, 2025)
The advocate in the mediation process is a companion or advisor. The role of an advocate in handling a case of breaking the law is an obligation to handle problems that are controlled by a person or party in a legal situation. One of the roles of advocates is to carry out mediation. Mediation is a series of legal settlement processes in which disputing parties meet directly and voluntarily to discuss and try to reach a peace agreement, of course this is assisted by an attorney, meaning that the attorney acts as a liaison between the client and the opposing party to make peace that benefits both parties. parties without having to carry out litigation in court or it can also be called making peace outside of court. The aim of the advocate's role in handling a case of breaking the law is basically inseparable from providing solutions and alternatives that can be taken by the litigant in accordance with the provisions, however the advocate does not have the authority to decide the outcome of a case or matter because of the role of the law. In this case, the litigants can carry out mediation which can be accompanied by an advocate to make peace according to the agreement between the parties concerned.